The Effect of Temperature and Heating Time to Antioxidant Activity of Onion Dayak Bulb Extract (Eleutherine palmifolia): Antioxidant Activity of Onion Dayak Bulb Extract (Eleutherine palmifolia) - Mutiara, Roza; Ulyarti, Ulyarti; Yulia, Ade (Jurnal Bio-Geo Material Dan Energi, 2023)
Onion Dayak (Eleutherine palmifolia) is a typical plant of center Kalimantanwhich has been used hereditary as medicine by Dayak people. The part of thisplant that is used as medicine is the bulb. Empirically, the bulb of onion Dayakcan heal diabetic disease, hypertension, cancer and lower cholesterol level. Theaimed of this study is to know the effect of heating temperature and heating timeto the antioxidant activity of onion Dayak bulb extract (Eleutherine palmifolia).This study was using a completely randomized design (CRD) with factorialpattern. Two factor used in this study were heating temperature (75, 85, 95 ºC)and heating time (5, 10, 15 minutes). This study was performed in threereplications. The result showed that heating temperature and heating time has asignificance effect on the yield, antioxidant activity value and IC50. Thetreatment of 75ºC for 5 minutes of heating was the best combination of heatingtemperature and heating time with the value yield (76,50%), antioxidant activityvalue (63,72%), IC50 (33,05µg/ml), color: L* 43,25, a*-2,01, b* 18,4.Phytochemical analysis showed that the extract of onion Dayak bulb containsphenolic and flavonoid compounds.